Textiles and their use in microbial protection focus on COVID-19 and other viruses - Periyasamy, Aravin Prince; Venkataraman, Mohanapriya; Militky, Jiri (Material engineer) (Boca Raton, FL CRC Press, 2021)
"Textiles and Their Use in Microbial Protection: Focus on COVID-19 and Other Viruses provides readers with vital information about disinfection mechanisms used in textile applications in the fight against dangerous microbes and viruses. It is aimed at textile and materials engineers as well as readers in medical fields and offers a comprehensive view of fundamentals and solutions"--
Introduction to textile materials used in healthcare / Jiri Militky, Mohanapriya Venkataraman and Aravin Prince Periyasamy -- Protection against microbes : state-of-the-art / Aravin Prince Periyasamy, Mohanapriya Venkataraman and Jiri Militky -- Virology of SARS-CoV-2 / Dan Wang, Dana Kremenakova, Jiri Militky -- Characterization, indication and passivation of COVID 19 / Sajid Faheem, Nazia Nahid, Muhammad Shah Nawaz ul Rehman, Jiri Militky, Jakub Wiener -- Disinfection mechanisms of UV light and ozonization / Yuanfeng Wang, Jiri Militky and Aravin Prince Periyasamy -- Influence of UV light and ozonization on microbes state / Xiaodong Tan, Qingyan Peng, Kai Yang, Jana Saskova, Aravin Prince Periyasamy, Jiri Militky and Jakub Wiener -- Photocatalysis and virus spreading / Aamir Mahmood, Jiri Militky and Miroslava Pechociakova -- Kinetic model for disinfection by using of photo-oxidation / Qingyan Peng, Mohanapriya Venkataraman and Jiri Militky -- Titanium dioxide : enhanced disinfection / Muhammad Zaman Khan, Jiri Militky, Jakub Wiener and Azam Ali -- Impact of copper and ions against coronavirus / Azam Ali, Saeed Ahmad, Jiri Militky, Hira Khaleeq, Muhammad Zaman Khan -- Copper coated textiles for viruses dodging / Shi Hu, Dana Kremenakova, Jiri Militky and Aravin Prince Periyasamy -- Eradicating spread of virus by using activated carbon / Daniel Karthik, Jiri Militky, Mohanapriya Venkataraman -- Antiviral finishes for protection against SARS-CoV-2 / Divan Coetzee, Mohanapriya Venkataraman, Jiri Militky -- Fundamental principles for moisture harvesting system and its design of fabric / Kai Yang, Mohanapriya Venkataraman, Jiri Militky.
Includes bibliographical references and index.
Keywords: Anti-infective agents; Biomedical materials; Disinfection and disinfectants; Industrial fabrics; Virus diseases -- Prevention